Dried artichoke bracts in rabbits nutrition: effects on the carcass characteristics, meat quality and fatty-acid composition. (13th June 2014) - Dabbou, S.; Gasco, L.; Gai, F.; Zoccarato, I.; Rotolo, L.; Dabbou Fekih, S.; Brugiapaglia, A.; Helal, A. N.; Peiretti, P. G.
<x content-type="archive" xml:space="preserve">Abstract</x> In this study, the effects of the inclusion of artichoke bracts (AB) in rabbit diets on the carcass characteristics and rabbit meat quality were studied. A total of 120 rabbits aged 38 days were used and divided into three groups that were fed with different isonitrogenous and isocaloric diets supplemented with AB at 0%, 5% and 10%. The animals were single housed in wire cages at a temperature of 22±2°C and had free access to clean drinking water. At 96 days of age, 12 rabbits/group were slaughtered in an experimental slaughterhouse without fasting. The carcass was weighed and the weights of the skin and full gastrointestinal tract were recorded. Carcasses were chilled at +4°C for 24 h in a refrigerated room. The chilled carcass weight (CCW), dressing out percentage (CCW as percentage of slaughter weight), and the ratio of the head and liver were determined as a percentage of CCW. The reference carcass weight was also calculated. Carcasses were halved and the two longissimus dorsi (LD) muscles were excised. The left LD muscle was divided into two parts. The fore part was used to measure pH, colour and cooking losses. The hind part of the left LD was vacuum-packed, frozen at –20°C and then freeze-dried. Proximate composition, fatty-acid profile and thiobarbituric acid-reactive substances values were determined on freeze-dried samples. Results showed that carcass characteristics, LD muscle traits and its oxidative status were not affected by the AB supplementation, except for the meat ether extract content that increased from 0.68% to 0.94% on fresh matter basis with the increase of the AB supplementation (P<0.01). The α-linolenic acid proportion decreased with the increase of the AB supplementation from 3.58% to 2.59% in the LD muscle and from 4.74% to 3.62% in the perirenal fat, whereas the n-6/n-3 ratio increased significantly with increasing AB inclusion from 7.15 to 10.20 in the LD muscle and from 6.68 to 9.35 in the perirenal fat (P<0.01). Furthermore, no significant difference was found in preference among meat samples from each group. The enrichment of the rabbit's diet with AB allows the production of rabbit meat with a good degree of unsaturation and low saturation, even if the n-6/n-3 ratio was slightly worse.